The association between body mass index and gastroesophageal reflux disease in the World Trade Center Health Program General Responder Cohort. Issue 9 (September 2016) - Icitovic, Nikolina; Onyebeke, Lynn C.; Wallenstein, Sylvan; Dasaro, Christopher R.; Harrison, Denise; Jiang, Jieying; Kaplan, Julia R.; Lucchini, Roberto G.; Luft, Benjamin J.; Moline, Jacqueline M.; Pendem, Lakshmi; Shapiro, Moshe; et al.
Abstract : Background: There is increasing concern about the obesity epidemic in the United States. Obesity is a potential risk factor for a number of chronic diseases, including gastroesophageal reflux disease (GERD). This analysis examined whether body mass index (BMI) was associated with physician‐diagnosed GERD in World Trade Center (WTC) general responders. Methods: 19, 819 WTC general responders were included in the study. Cox proportional hazards regression models were used to compare time to GERD diagnosis among three BMI groups (normal (<25 kg/m 2 ), overweight (≥25 and <30 kg/m 2 ), and obese (≥30 kg/m 2 )). Results: Among the responders, 43% were overweight and 42% were obese. The hazard ratio for normal versus overweight was 0.81 (95% Confidence Interval (CI), 0.75–0.88); normal versus obese 0.71 (95%CI, 0.66, 0.77); and overweight versus obese 0.88 (95%CI, 0.83–0.92). Conclusion: GERD diagnoses rates were higher in overweight and obese WTC responders. Am. J. Ind. Med. 59:761–766, 2016. © 2016 Wiley Periodicals, Inc.